Bacterial Factors Affecting Newborns with Septicemia - Ibraheem , Ali Jasim; Abid , Jawad Kadhum; Shimal, Taghreed Fadhil (International Journal of Psychosocial Rehabilitation, 2020)
Most newborn infections are caused by bacteria. Bacteria live naturally in the birth canal, and the baby is exposed to them during birth. The newborn may swallow or breathe the fluid into the birth canal, after which the bacteria may enter the baby’s lungs and bloodstream. Neonatal sepsis is one of the most common causes of death and morbidity in newborns, especially in developing countries. The bacteria that cause it and their allergic patterns differ in each hospital and region. Conclusion: Attention after contamination occurs along with Staphylococcus epidermidis in these instructions or similar studies, with correct use of antibiotics because treating and following up on hygiene concepts in pediatric or neonatal departments may reduce mortality and injury caused by disease use. Treatments are based on medication selection and appropriate antimicrobial dosage, supportive therapy, fluid therapy, non-steroidal anti-inflammatory drugs, and plasma transfusions. Preventing passive transport failure through good colostrum management is essential.